Implementing a second generation CCS facility on a coal fired power station – results of a feasibility study to retrofit SaskPower's Shand power station with CCS. Issue 3 (26th May 2020) - Giannaris, Stavroula; Bruce, Corwyn; Jacobs, Brent; Srisang, Wayuta; Janowczyk, Dominika
Abstract: In 2018, the International CCS Knowledge Centre (CCS Knowledge Centre) conducted a feasibility study with SaskPower to determine if a business case could be made for a postcombustion, carbon capture retrofit of SaskPower's Shand Power station, a 305‐MW, single‐unit, lignite coal‐fired power station located near Estevan, Saskatchewan. Specifically, Mitsubishi heavy industries' KM CDR technology was evaluated for this study. While no decision has been made, should SaskPower decide to proceed, the Shand carbon capture and storage (CCS) project would produce the second, full‐scale capture facility in Saskatchewan with a nominal capacity of 2 million tonnes of CO2 (Mt) per year. This paper summarizes the key technical and economic findings of this study. Notably this study found that the capital costs of the potential Shand CCS facility are decreased by 67% on a per tonne of CO2 captured basis when compared to the CCS retrofit of Unit 3 at the Boundary Dam Power Station (the world's first industrial scale CCS installation on a coal fired power station). The proposed capture facility would also have a load following operational profile, reduction in parasitic loses by employing heat integration strategies, and need no additional water draw to provide the required increase in cooling duty. © 2020 The Authors. Greenhouse Gases: Science and Technology published by Society of Chemical Industry and John Wiley & Sons, Ltd.